Outcomes associated with antithrombotic strategies in heart failure with reduced ejection fraction and sinus rhythm following acute ischemic stroke - Patel, Parth; Tiongson, Justin; Chen, Austin; Siegal, Taylor; Oak, Solomon; Golla, Akhil; Kamen, Scott; Thon, Jesse M.; Vigilante, Nicholas; Rana, Ameena; Hester, Taryn; Siegler, James E. (Frontiers in Neurology, 2022)
Purpose: In patients with ischemic stroke and heart failure with reduced ejection fraction (HFrEF), there is insufficient data regarding the benefit of long-term antiplatelet versus anticoagulant therapy in the prevention of recurrent ischemic stroke. The purpose of this study is to compare longitudinal outcomes associated with antiplatelet versus anticoagulant use in a cohort of stroke patients with an ejection fraction ≤40%. Methods: We retrospectively analyzed single-center registry data (2015-2021) for patients with ischemic stroke, HFrEF, and sinus rhythm. Time to the primary outcome of recurrent ischemic stroke, major bleeding, or death was assessed using adjusted cox proportional hazards modeling and compared between patients treated using anticoagulation (± antiplatelet) versus antiplatelet therapy alone after propensity score matching using an intention-to treat (ITT) approach, with adjustment for residual measurable confounders. Sensitivity analyses included multivariable cox proportional hazards modeling using ITT and as-treated approaches without propensity score matching. Results: Of the 2974 screened patients, 217 were included in the secondary analyses, with 130 patients matched according to propensity for receiving anticoagulation, spanning 143 patient-years of follow-up. After propensity score matching, there was no significant association between anticoagulation and the primary outcome (hazard ratio [HR] 1.10, 95% confidence interval [CI] 0.56-2.17). Non-White race (HR 2.26, 95%CI 1.16-4.41) and presence of intracranial occlusion (HR 2.86, 95%CI 1.40-5.83) were independently associated with the primary outcome, while hypertension was inversely associated (HR 0.42, 95%CI 0.21-0.84). There remained no significant association between anticoagulation and the primary outcome in sensitivity analyses. Conclusions: In patients with HFrEF found to have an acute stroke, there was no difference in outcomes by antithrombotic strategy. While these data are non-randomized, they support equipoise in randomizing patients with HfrEF and acute stroke to anticoagulation or antiplatelet therapy in future clinical trials.